Odpowiedzi

2010-01-20T16:45:10+01:00
A) 6b-1+2b=7b+5
8b-7b=5+1
b=6
B) 0,4y+1,3-0,6=1,3-0,8y
0,4y+0,8y=0,6
1,2y=0,6
y=1/2
1 1 1
2010-01-20T16:47:35+01:00
A) 6b - (1-2b) = 7b+5
6b - 1 + 2b = 7b + 5
6b + 2b - 7b = 5 + 1
b = 6

b) 0.4 ( y+13) - 0.6 = 1.3 - 0.8y
0.4y + 5.2 - 0.6 = 1.3 - 0.8y
0.4y + 0.8y = 1.3 - 5.2 + 0.6
1.2y = -3.3
y = - 2.75

@up
0.4 × 13 = 5.2, a nie 1.3
1 1 1
Najlepsza Odpowiedź!
2010-01-20T16:53:06+01:00
A)6b - (1-2b) = 7b+5 <--redukuję nawias
6b-1+2b=7b+5 <--przenoszę niewiadome na lewą stronę
6b+2b-7b=5+1
b=6

b) 0.4 ( y+13) - 0.6 = 1.3 - 0.8y <---wymnażam 0.4 przez nawias
0.4y+5.2-0.6=1.3-0.8y <---przenoszę niewiadome
0.4y+0.8y=1.3-5.2+0.6
1.2y= -3.3 /:1.2 <---dzielę obie strony przez 1.2
y= -2,75